Stratified glucocorticoid monotherapy is safe and effective for most cases of giant cell arteritis. Issue 2 (12th June 2020) - Karabayas, Maira; Dospinescu, Paula; Locherty, Marc; Moulindu, Paul; Sobti, Manvi; Hollick, Rosemary; De Bari, Cosimo; Robinson, Susan; Olson, John; Basu, Neil
Abstract: Objectives: High-dose glucocorticoids anchor standard care in GCA but are associated with significant toxicity. We aimed to evaluate the safety and effectiveness of a stratified approach to glucocorticoid tapering. The strategy aggressively reduced glucocorticoid doses in those manifesting an adequate early response to treatment, with a view to minimizing glucocorticoid complications. Methods: A retrospective, population-based study of GCA was performed. All cases were confirmed by temporal artery biopsy between November 2010 and November 2015. Baseline and outcome data were extracted from secondary and primary care records at diagnosis and 1 year follow-up. The primary outcome was loss of vision. Secondary outcomes included remission and relapse rates and CS-related complications. Results: The cohort consisted of 73 patients (76% female; mean age 73.5 years, s .d . 7.6 years). At presentation, a reduction in visual acuity was recorded in 17 patients (22.3%). The median CRP at diagnosis was 69.5 mg/l [interquartile range (IQR) 40.5–101 mg/l], with a median ESR of 80 mm/h (IQR 60–91 mm/h). At 1 year, remission was achieved in 64 patients (87.7%), whereas 10 patients (13.7%) relapsed. A single patient sustained visual loss after initiation of therapy. The median CRP at 1 year was 4 mg/l (IQR 4–9.5 mg/l) and the mean prednisolone dose was 5.4 mg (0–15 mg). CS-related complications were observed in 10 patients (13.7%). Conclusion: A stratified approach to CS tapering appeared safe and effective in GCA. It was associated with a high rate of remission and promisingly low rates of relapse at 1 year follow-up. These real-world data indicate that glucocorticoid exposure can be minimized safely in some patients with GCA.